Spatio-Temporal Variation of Synechococcus Assemblages at DNA and cDNA Levels in the Tropical Estuarine and Coastal Waters - Wang, Ting; Xia, Xiaomin; Chen, Jiawei; Liu, Hongbin; Jing, Hongmei (Frontiers in Microbiology, 2022)
Synechococcus is a major contributor to global marine primary production. Here, its spatio-temporal variations in abundance and phylogenetic structure were studied at three stations of the South China Sea at both DNA and cDNA levels. Synechococcus cell abundance was lowest in March, but highest in October at two coastal stations. Its abundance was higher at the estuarine station, which reached a peak value of 1.36 × 105 cells/mL in April, owing to the nitrogen nutrients discharged from the Sanya River. Gene and gene transcript abundances of four Synechococcus lineages, clades II, III, VIII, and S5.3, were studied by quantitative PCR, which showed that clade II was the most abundant lineage at both DNA and cDNA levels. High-throughput sequencing revealed that, at the DNA level, Synechococcus assemblage was dominated by clade SY4 (a novel clade defined in this study), S5.2, and clade II in the coastal waters and was dominated by freshwater/S5.2 Synechococcus, reaching a value up to 88.61% in June, in estuarine waters,. Changes in salinity and nutrient concentration caused by seasonal monsoonal forcing and river discharge were the key determinants of the spatio-temporal variation in Synechococcus assemblages at the DNA level. In comparison, high dissimilation among samples at the same stations and in the same seasons lead to the imperceptible spatio-temporal variation pattern of Synechococcus assemblages at the cDNA level. Furthermore, co-occurrence networks disclosed that Synechococcus community had closer and more complex internal interactions at the cDNA level. These discrepancies highlighted the necessity to study Synechococcus assemblages at both DNA and cDNA levels.